Two new species of Thrypticus Gerstäcker from Turkey (Diptera, Dolichopodidae), with checklist and key to Palaearctic species - Negrobov, Oleg P.; Naglis, Stefan (Zootaxa, 2020)
Thrypticus caeruleus Naglis & Negrobov sp. nov. and T. kechevi Naglis & Negrobov sp. nov. are newly described from Turkey. Thrypticus viridis Parent is redescribed and the hypopygium is figured in detail. A revised checklist and key to males of Palaearctic species of the genus Thrypticus Gerstäcker including 26 valid species are provided. Thrypticus paludicola Negrobov is restored from synonymy with T. intercedens Negrobov based on hypopygial differences. Thrypticus tonsus Negrobov is regarded as new synonym of T. subtilis Negrobov.